Study of the Effect of the Polymer Preparation of Quicksets in Fergana Province - V.K.Rakhmonberdiev; A.Kh.Ruziev; M.I.Ruzieva (Zien Journals, 2022)
The main problem in vegetatively propagated plants is the formation of callus. Therefore, in our experiments, we tried to use a preparation that accelerates the formation of callus in mulberry quicksets. The preparation "ADENIN" with its polysaccharides and biologically active substances accelerates the encapsulation and, as a result, the protection of the quicksets from the external environment, as well as the decay of the quicksets.
Keywords: Mulberry varieties; biologically active polymeric preparation; shoot; substances